Growth of Care Characters in the Lisambil Discussion of Student in Smp Negeri 21 Pekanbaru - Deswati Deswati; Suwondo Suwondo; Firdaus LN (Universitas Riau, 2020)
The character of caring for students environment is still low. The study aims to evaluate the growth of environmental care character of students, at SMP Negeri 21 Pekanbaru. The parameters of research were the perception of teachers, principals, students and the growth of environmentally conscious character aspects of the action of growing brothers caring for the environment and environmental cleanliness after the action. The results of the study shows the teacher perceptions with average of 4.44 (88%) in the good category. The school principals is 4.69 (94%) in the good category and student score is 4.24 (79%) in the good category. Students perception of habituation aspects before KBM averaged a score of 1.90 (63%) enough category. The act of growing character cares for the environment with an average of 69% (good), in the aspect of implementation of the class picket the average is 56% (enough). Environmental hygiene in the class average of 77% (good), in terms of cleaning activities before KBM averaged 60% (enough). Environmental cleanliness with an average of 28.7% (less). The growth of students environmental care character from caring actions is showing in the good category and environmental cleanliness in the classroom category is sufficient and outside the classroom category is lacking.